2002
DOI: 10.1002/cncr.10381
|View full text |Cite
|
Sign up to set email alerts
|

Direct visual inspection for cervical cancer screening

Abstract: BACKGROUNDThe authors evaluated direct visual inspection of the cervix after the application of 5% acetic acid (DVI) as a cervical cancer screening test for use in low‐resource settings.METHODSFour tests were used to screen 2754 previously unscreened women: DVI with and without ×4.5 magnification and differentiating between all lesions and well‐circumscribed lesions; testing for high‐risk types of human papillomavirus DNA using the Hybrid Capture II assay, cervical cytology, and Cervicography™. Women with posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 137 publications
(32 citation statements)
references
References 17 publications
3
24
2
Order By: Relevance
“…As discussed above, this is a population of considerable gynecological ill-health with high rates of HIV, HPV, cervical neoplasia, and other sexually transmitted infections (Denny, Kuhn, Pollack, & Wright, 2002). Women in our sample revealed concerns about their own gynaecological problems, with more than half reporting having vaginal problems and one third reporting having "womb" problems in the previous 12 months.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…As discussed above, this is a population of considerable gynecological ill-health with high rates of HIV, HPV, cervical neoplasia, and other sexually transmitted infections (Denny, Kuhn, Pollack, & Wright, 2002). Women in our sample revealed concerns about their own gynaecological problems, with more than half reporting having vaginal problems and one third reporting having "womb" problems in the previous 12 months.…”
Section: Discussionmentioning
confidence: 68%
“…This is a population of considerable ill-health: Recent prevalence rates for HIV and other sexually transmitted infections were found to be 7% and 25%, respectively, in women aged 35-65 recruited in the Khayelitsha Cervical Cancer Screening Project (KCCSP). Cervical cancer in the same population was 0.8%, and the prevalence of high and low grade squamous intraepithelial lesions was 3.5% and 3.7%, respectively, with 20% positive for high-risk types of the human papilloma virus (HPV) DNA (Denny, Kuhn, Pollack, & Wright, 2002). A study of 659 women in Khayelitsha in [1989][1990] showed that 55% of women had never had a cervical smear .…”
Section: Study Areamentioning
confidence: 99%
“…The difference between the two scenarios is most likely due to having a system of tracking women with abnormal smears to ensure appropriate followup. Denny et al 40 showed an over 90% return rate post screening in a research setting where intense attention was paid to recording women's contact details, home addresses etc. and women who defaulted were tracked within a week of their missed appointment, suggesting that mechanisms for recalling women with abnormal smears for further investigation and treatment is as essential a part of the structure of a screening programme as is high quality laboratory services.…”
Section: Tek Images / Science Photo Librarymentioning
confidence: 99%
“…Screening is sporadic in developing countries and has tended to be opportunistic, with little impact on the incidence of cervical carcinoma. 10 3 Different studies have shown that cervical cancer is an important but hidden health problem in Iran.…”
Section: Which Recorded 23 Invasive Carcinoma Per 1000 Pap Test Exammentioning
confidence: 99%